2015
DOI: 10.1016/j.foodqual.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Investigating individual preferences in rating and ranking conjoint experiments. A case study on semi-hard cheese

Abstract: Order of Authors: Valérie L Almli, MSc.; Arnstein Øvrum, MSc.; Margrethe Hersleth, Ph.D.; Trygve Almøy, Ph.D.; Tormod Naes, Ph.D.Abstract: Stated preference conjoint experiments and self-explicated measures based on rating and ranking approaches were conducted to investigate Norwegian consumers' choices among healthier and organically produced semi-hard cheeses. In the conjoint experiments, one group of participants (n=114) performed a rating task of eight cheeses whereas the other group (n=105) performed a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
2
20
0
5
Order By: Relevance
“…The importance given by consumers to the selected claims when shopping two based cereal products was assessed using a direct ranking preference method with primary data from a survey administrated to consumers in a region of Spain in 2017. As prior research has identified that preferences for nutritional claims are heterogeneous across consumers [12][13][14][15][16] and products [17], the specification of the model accommodates differences in preferences across both domains.…”
Section: Introductionmentioning
confidence: 99%
“…The importance given by consumers to the selected claims when shopping two based cereal products was assessed using a direct ranking preference method with primary data from a survey administrated to consumers in a region of Spain in 2017. As prior research has identified that preferences for nutritional claims are heterogeneous across consumers [12][13][14][15][16] and products [17], the specification of the model accommodates differences in preferences across both domains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, consumers are reported to focus on sensory quality in locally produced cheeses (Enneking et al, 2007;Koutroulou and Tsourgiannis, 2011;Aquilanti et al, 2013;Goosen and Muller, 2014) and on nutritional values Goosen and Muller, 2014;Tsourgiannis et al, 2014;Almli et al, 2015;Miklavec et al, 2015;Topcu, 2015;Pinto et al, 2016). All these studies support the findings of the current study with regard to the impact of intrinsic product attributes on Erzurum Civil cheese purchasing decisions, with heavy users gaining increased satisfaction from core benefits.…”
Section: Results Of Multiple Regression and Correlation (Mrc) Analysesmentioning
confidence: 99%
“…PGI güvence unsuru, tüketici taleplerinin artmasından kaynaklanan potansiyel kaynakların harekete geçirilmesi ve sürdürülebilir arz zincirinin temin edilmesi ile kırsal ve bölgesel kalkınmaya katkı sağlanabilir. Mevcut çalışma sonuçları ile uyumlu olarak yerel gıda ürünleri, kırsal ekonomilerin canlandırılmasına ve sürdürülebilir kırsal kalkınmanın sağlanmasına potansiyel oluşturmaktadır (Callois, 2004;Topcu et al, 2010;Topcu, 2012aTopcu, ve 2012b Almli et al, (2015); PDO, PGI ve TSG etiketli yerel gıda ürünlerinin daha hijyenik/sağlık kriterlerine uygun gıda konteksine göre gıda güvenliği garantisi ile talep trendlerinin arttığına ve piyasada önemli bir hacime ulaştığına vurgu yapmıştır.…”
Section: Verilerin Istatistiksel Analizinde Uygulanan Yöntemlerunclassified
“…Bu durumda Erzurum Civil peyniri tüketim kararları üzerinde duyusal kalitenin görsel kaliteden daha büyük bir etkiye sahip olduğu analiz edilmiştir. Özellikle tüketim çalışmalarında gıda ürünlerinde duyusal kalitenin diğer kalite olgularından çok daha büyük bir önem arz ettiği, daha önce yapılmış çeşitli çalışmalarda ortaya konulmuştur (Topcu, 2012a;Pugliese et al, 2013;Almli et al, 2015;Topcu, 2015).…”
Section: Verilerin Istatistiksel Analizinde Uygulanan Yöntemlerunclassified